Emissions of anthropogenic pollutants and their environmental concentrations in Alpine areas : trends under climate change assumptions - Teran Guerrero, Tair Dolores (Università Ca' Foscari Venezia, 2015)
Evidence of climate change has been observed at both the global and local scales. It includes changes in surface temperatures and ice cover in the Arctic, widespread changes in precipitation pattern and amounts, ocean salinity, wind patterns and incidents of extreme weather including droughts, heavy precipitation, heat waves and intensity of tropical cyclones. Climate variables influence the status of the ecosystem and this may negatively influence the ecosystem services, and this may accordingly be affecting human systems. In this context, this Ph.D. thesis aims at contributing to the assessment of the impacts of climate change in influencing anthropogenic pollutants’ concentration, in particular POPs, in high-altitude regions, in order to identify which atmospheric conditions could be impacted by those climatic changes and affect the relationship between source and sink at high altitudes into remote alpine environments. In chapter 2 a critical review is presented regarding the effects of climate change on the POPs’ regulation efforts driven towards decreasing POPs’ behaviour through reducing or banning POPs’ emissions in the environment. In chapter 3, a novel database and a data managing system is presented for the collection of POPs' concentrations on monitoring data available for European Alps is presented. Through this system, it was possible to collect relevant environmental and chemical information useful for the subsequent application of a multimedia fate and transport model of POPs. Chapter 4 is devoted in describing the modelling and application of a multimedia fate and transport model, named MountainPOP3.0 in order to assess the effect of climate change on POPs' environmental distribution. In addition, an application of our MountainPOP3.0 model to a case of study is presented. The case study was based on Adda River enclosed in a mountainous region in the Northern Italian Alps. The substances evaluated during this approach were alpha-Hexachlorocyclohexane (alpha HCH) and Hexachlorobenzene (HCB). ...